Dosimetric analysis of half-field-based VMAT with the deep inspiration breath-hold technique for left breast cancer patients following breast-conserving surgery - Wu, Weiwei; Yin, Hui; Liu, Zhiwei; Liu, Lipeng; Xiao, Chengjian; Xiao, Ying; Ding, Jinquan; Zhang, Qungui; Guo, Hailiang (Frontiers in Oncology, 2024)
ObjectiveCompared the dosimetric characteristics of half-field-based VMAT and half-field-based IMRT for left breast cancer patients combined with deep inspiration breath-hold (DIBH) and free breathing (FB) techniques.MethodsTwenty-one left breast cancer patients were included. Each patient underwent DIBH and FB CT scans, IMRT and VMAT plans in half-field beam mode for both breathing techniques, resulting in four plans: FB-IMRT (F-IMRT), FB-VMAT (F-VMAT), DIBH-IMRT (D-IMRT) and DIBH-VMAT (D-VMAT). The conformity index (CI), homogeneity index (HI), and the doses received at the heart, left anterior descending (LAD), left lung, right breast, and right lung, were compared among plans.The correlation between the difference in the volume of lung_L (ΔLVL) and the difference in the mean dose (ΔDmean) of lung_L under the DIBH and FB plans, the correlation between the difference in the heart-chest distance (ΔHCD) and the ΔDmean of the heart,LAD under the DIBH and FB plans.ResultsThe D-VMAT plan lower lung_L V5 than both the F-IMRT and F-VMAT plans (p<0.05), The D-VMAT plan lower values for V10, V20, V30, and Dmean than did the other plans (p < 0.05). For the heart, the D-VMAT plan lower V5, V10, V20, and Dmean values than did the other plans (p < 0.05). The D1% and Dmax of the heart and the Dmax and Dmean of the LAD obtained with the D-VMAT plan were lower than those obtained with the F-IMRT and F-VMAT plans (p < 0.05). ΔHCD exhibited correlation with the ΔDmean of the LAD between the D-VMAT and F-IMRT plans and between the D-VMAT and F-VMAT plans (R = -0.765 and -0.774, respectively, p = 0.000).Conclusionthe D-VMAT plan offered enhanced protection for OARs. The integration of the DIBH technique with half-field and VMAT technology in the D-VMAT plan offers a superior dose distribution.